Saurenchelys gigas sp. nov., a new nettastomatid eel (Teleostei, Anguilliformes, Nettastomatidae) from the western central Pacific - Lin, James; Smith, David G.; Shao, Kwang-Tsao; Chen, Hong-Ming (Zootaxa, 2015)
Some large Saurenchelys specimens collected from Daxi, Yilan, NE Taiwan, and Da Nang, Vietnam, by bottom trawl at depths of 100–200 m, are described as Saurenchelys gigas new species. They differ from all known adult Saurenchelys species by predorsal length 40.9–46.8, head length 36.8–39.3in % of preanal length, 38–40 preanal vertebrae, 63–70 precaudal vertebrae, 38–42 preanal lateral-line pores, 56–63 preanal dorsal fin rays, and larger size (the maximum size 1155 mm TL).